Hydrogen Inverse Z-Pinch at the High-Current Generator MIG; 13 International symposium on high current electronics - Bystritsky V. M.; Bystritskii Vit. M.; Dudkin G. N. Gennadiy Nikolaevich; Gerasimov V. V.; Mesyats G. A. Gennady Andreyevich; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Parzhitsky S. S.; Ratakhin N. A. Nikolay Aleksandrovich; Stolupin V. A.; Volkov E. N.; Wozniak J. (Pinches, plasma focus and capillary discharge, 2004)
Title from the title-page.